Multiple Sources of the Outbreak of Legionnaires’ Disease in Genesee County, Michigan, in 2014 and 2015 - Smith, Anya F.; Huss, Anke; Dorevitch, Samuel; Heijnen, Leo; Arntzen, Vera H.; Davies, Megan; Robert-Du Ry van Beest Holle, Mirna; Fujita, Yuki; Verschoor, Antonie M.; Raterman, Bernard; Oesterholt, Frank; Heederik, Dick; et al. (Environmental health perspectives, 2019)
A community-wide outbreak of Legionnaires' disease (LD) occurred in Genesee County, Michigan, in 2014 and 2015. Previous reports about the outbreak are conflicting and have associated the outbreak with a change of water source in the city of Flint and, alternatively, to a Flint hospital. The objective of this investigation was to independently identify relevant sources of that likely resulted in the outbreak. An independent, retrospective investigation of the outbreak was conducted, making use of public health, health care, and environmental data and whole-genome multilocus sequence typing (wgMLST) of clinical and environmental isolates. Strong evidence was found for a hospital-associated outbreak in both 2014 and 2015: ) 49% of cases had prior exposure to Flint hospital A, significantly higher than expected from Medicare admissions; ) hospital plumbing contained high levels of ; ) control measures in hospital plumbing aligned with subsidence of hospital A-associated cases; and ) wgMLST showed isolates from cases exposed to hospital A and from hospital plumbing to be highly similar. Multivariate analysis showed an increased risk of LD in 2014 for people residing in a home that received Flint water or was located in proximity to several Flint cooling towers. This is the first LD outbreak in the United States with evidence for three sources (in 2014): ) exposure to hospital A, ) receiving Flint water at home, and ) residential proximity to cooling towers; however, for 2015, evidence points to hospital A only. Each source could be associated with only a proportion of cases. A focus on a single source may have delayed recognition and remediation of other significant sources of . https://doi.org/10.1289/EHP5663.